KRITIK TERHADAP PSAK PERBANKAN SYARIAH IAI DAN AAOIFI - Sofyan Syafri Harahap (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2001)
The Conceptual framework for presentation of financial statement of Islamic bank and Accounting standards for Islamic banking have been formulated by Indonesian Asso-ciation of Accountants (cooperated with Bank Indonesia, Indonesia central bank.. The standards are called PSAK (Pemyataan Standard Akuntansi Keuangan). The frame-work and the standards, mainly, has refered to the MOIFI standard for Islamic bank-ing. This paper discusses the the content of the those two promulgations (MOIFI and PSAK) and also criticizes the lack of lawhid